The replication initiator operon of promiscuous plasmid RK2 encodes a gene that complements an Escherichia coli mutant defective in single-stranded DNA-binding protein. - Jovanovic, O S (1992)
The amino acid sequence of the 13-kDa polypeptide (P116) encoded by the first gene of the trfA operon of IncP plasmid RK2 shows significant similarity to several known single-stranded DNA-binding proteins. We found that unregulated expression of this gene from its natural promoter (trfAp) or induced expression from a strong heterologous promoter (trcp) was sufficient to complement the temperature-sensitive growth phenotype of an Escherichia coli ssb-1 mutant. The RK2 ssb gene is the first example of a plasmid single-stranded DNA-binding protein-encoding gene that is coregulated with replication functions, indicating a possible role in plasmid replication.